Fabrication and characterization of a novel carbon fiber-reinforced calcium phosphate silicate bone cement with potential osteo-inductivity. (23rd December 2015) - Zheng, Jiangjiang; Xiao, Yu; Gong, Tianxing; Zhou, Shuxin; Troczynski, Tom; Yang, Quanzu; Bao, Chongyun; Xu, Xiaoming
Abstract: The repair of bone defects is still a pressing challenge in clinics. Injectable bone cement is regarded as a promising material to solve this problem because of its special self-setting property. Unfortunately, its poor mechanical conformability, unfavorable osteo-genesis ability and insufficient osteo-inductivity seriously limit its clinical application. In this study, novel experimental calcium phosphate silicate bone cement reinforced by carbon fibers (CCPSC) was fabricated and characterized. First, a compressive strength test and cell culture study were carried out. Then, the material was implanted into the femoral epiphysis of beagle dogs to further assess its osteo-conductivity using a micro-computed tomography scan and histological analysis. In addition, we implanted CCPSC into the beagles' intramuscular pouches to perform an elementary investigation of its osteo-inductivity. The results showed that incorporation of carbon fibers significantly improved its mechanical properties. Meanwhile, CCPSC had better biocompatibility to activate cell adhesion as well as proliferation than poly-methyl methacrylate bone cement based on the cell culture study. Moreover, pronounced biodegradability and improved osteo-conductivity of CCPSC could be observed through the in vivo animal study. Finally, a small amount of osteoid was found at the heterotopic site one month after implantation which indicated potential osteo-inductivity of CCPSC. In conclusion, the novel CCPSC shows promise as a bioactive bone substitute in certain load-bearing circumstances.